Spiritual Values in The Economic Practices of Al-Bahjah Students in Central Cirebon - Neng Ulpa Apipah; Rosidah Rosidah; Umamah Mumtazah Askhiyah; Tarudi Tarudi; R. Ilfan Muhammad Abdurrasyid (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Pesantren in Indonesia function not only as centers of religious learning but also as spaces for forming Islamic-based economic values. Despite growing scholarly interest in pesantren entrepreneurship, the spiritual dimensions underpinning santri economic practices remain empirically underexplored. This study aims to explore the spiritual values embedded in the economic practices of santri at Al-Bahjah Islamic Boarding School, Central Cirebon, and to understand how these values shape the pesantren's economic culture. Methods: A qualitative case study design incorporating ethnographic techniques was employed. Data were collected through participatory observation and semi-structured in-depth interviews with three purposively selected informants — one institutional treasurer and two active santri — over three days (27–29 October 2025). Findings reveal that economic activities within the pesantren serve not merely as financial transactions but as a medium of moral and spiritual education. Core values — honesty (ash-shidq), trustworthiness (al-mas'uliyyah), blessing (al-barakah), and mutual help (ta'awun) — underpin every economic interaction. Distinctive practices including e-money as a moral governance instrument, integration of sholawat and dhikr into economic activities, and selective procurement of goods free from pro-Israel products constitute an economy grounded in spirituality and social accountability. The economic practices of Al-Bahjah santri represent a manifestation of spiritual economy that integrates economic, moral, and theological dimensions within a single cultural practice, offering an alternative paradigm that enriches Islamic economics discourse rooted in pesantren culture.